Calcium Phosphate-Based Bioceramics in the Treatment of Osteosarcoma: Drug Delivery Composites and Magnetic Hyperthermia Agents - Oliveira, Tiê Menezes; Berti, Fernanda Costa Brandão; Gasoto, Sidney Carlos; Schneider, Bertoldo; Stimamiglio, Marco Augusto; Berti, Lucas Freitas (Frontiers in Medical Technology, 2021)
The use of biomaterials in medicine is not recent, and in the last few decades, the research and development of biocompatible materials had emerged. Hydroxyapatite (HAp), a calcium phosphate that constitutes a large part of the inorganic composition of human bones and teeth, has been used as an interesting bioceramic material. Among its applications, HAp has been used to carry antitumor drugs, such as doxorubicin, cisplatin, and gemcitabine. Such HAp-based composites have an essential role in anticancer drug delivery systems, including the treatment of osteosarcoma. In addition, the association of this bioceramic with magnetic nanoparticles (MNPs) has also been used as an effective agent of local magnetic hyperthermia. Further, the combined approach of the aforementioned techniques (HAp scaffolds combined with anti-tumor drugs and MNPs) is also an attractive therapeutical alternative. Considering the promising role of the use of bioceramics in modern medicine, we proposed this review, presenting an updated perspective on the use of HAp in the treatment of cancer, especially osteosarcoma. Finally, after giving the current progress in this field, we highlight the urgent need for efforts to provide a better understanding of their potential applications.